Vienna (looking across the Glacis) - Cousen, Charles, 1815-1889 (engraver):::Creator::::::::::::; Bartlett, William Henry, 1809-1854 (artist):::Contributor::::::::::::; Beattie, William, 1793-1875 (author)::::::::::::::: (United Kingdom; George Virtue; London)
Engraving with view of the city of Vienna from a distance, with carriages, horses, and pedestrians on a road in the outskirts.